180 Days of Spelling and Word Study for First Grade : Practice, Assess, Diagnose. - Rhoades, Shireen Pesez (180 Days of Practice Ser., 2019)
Provide first grade students with 180 days of daily practice to build their knowledge of spelling rules, conventions, and patterns. Students gain regular practice with word study through the quick, diagnostic-based activities in this workbook.